Usulan Strategi Pengembangan Industri Pengolahan Kelapa Skala IKM di Kabupaten Indragiri Hilir - Khairul Ihwan; Nilda Tri Putri; Jonrinaldi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
The majority of the population in Indragiri Hilir (Inhil) already rely on palm plantations as the main income. They have already sold in the form of coconut oil and copra round with a relatively low price and is unable to provide a decent life. It is increasing because of the low level of productivity of coconut plantations and commercial systems that are less profitable for farmers. While in other areas of the coconut is a commodity that can be processed into a wide range of high-value products with simple technologies that can be done by small and medium industries. So, we need development strategies IKM-scale oil processing industry which is able to increase the income of coconut farmers in the district of Inhil. Based on the results of research conducted by the method of SWOT analysis produced 23 alternative strategies of the development of the SME scale oil processing industry in Kabupaten Inhil ie three strategies from SO, nine strategies from WO, seven strategies from ST, four strategies from WT. Based on the results of the weighting using Analytical Network Process (ANP) on any alternative strategy, Strategy SO-2 namely